Self-Development in Theatre Division Members of the Arts Student Activity Unit at Bhayangkara University, Jakarta Raya - Herliana Diah Ayuningsih; Widya Ningtyas; Arfian; Nadzifah Humaira (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Background: The Theater Division of the Ubhara Jaya Arts Club is currently undertaking a self-development program for its members. The abilities and quality of an organization's human resources determine its success. These abilities and qualities are derived from self-development processes and a strong determination, willingness, or desire to grow. Purpose: This paper aims to provide an understanding of the self-development process undertaken by the members of the Theater Division of the Ubhara Jaya Arts Club. Design/methods/approach: A qualitative method was employed. Data collection was conducted through interviews with the members. Findings: In the self-development process of the Ubhara Jaya Arts Club Theater Division members, it is crucial to have the desire to grow, engage in self-diagnosis, set targets, seek development resources, implement programs, conduct evaluations, and manage oneself and one's emotions. These factors contribute to the members' development in the theatrical arts.